Effects of Tidally Varying Salinity on Groundwater Flow and Solute Transport: Insights From Modelling an Idealized Creek Marsh Aquifer. Issue 11 (23rd November 2019) - Xiao, Kai; Li, Hailong; Xia, Yuqiang; Yang, Jinzhong; Wilson, Alicia M.; Michael, Holly A.; Geng, Xiaolong; Smith, Erik; Boufadel, Michel C.; Yuan, Ping; Wang, Xuejing
Abstract: Most existing numerical research on tide‐induced groundwater dynamics assumes a constant surface water salinity on the seaward boundary (constant salinity case). Few studies have investigated the influence of tidally varying salinity on shallow groundwater dynamics in coastal aquifers (tidal salinity case). We compiled field observations of tidally varying salinity in multiple estuaries across the eastern coast of China and a tidal creek in North Inlet‐Winyah Bay, United States. Numerical simulations were then conducted to explore the effect of tidally varying salinity on groundwater flow and salt transport in an idealized creek marsh aquifer. Results showed that the upper saline plume and classical saltwater wedge appeared in all cases, but the salinity in the saltwater wedge was diluted in the tidal salinity cases. Notably, groundwater transit times were shorter in the tidal salinity case than in the constant salinity case, especially under the creek bottom. Quantitative analyses indicated that tidally varying salinity significantly enhanced surface water‐groundwater exchange, increasing submarine groundwater discharge by 10% and the total inflow of surface water across the water‐sediment interface by 7%. As the density of groundwater differs from that of the overlying surface water, fingered saltwater flow formed in sediments under the creek bottom, leading to some small local water circulation cells. These small cells reduced groundwater transit times and almost doubled the water exchange rate. Coupling the density‐dependent flow to a simplified nitrogen reaction network revealed that the tidally varying salinity may have the potential to influence nitrogen biogeochemical transformations that modify nitrogen loads prior to discharge. Key Points: A large salinity gradient causes unstable density fingering in sediments under the creek bottom Unstable flow enhances local water circulation and reduces groundwater transit times Tidally varying salinity enhances surface water‐groundwater exchange and has the potential to modify nitrogen loads prior to discharge